Textbook Evaluation on Curriculum 2013-Based Textbook When English Rings A Bell for the Seventh Grade - Surtikanti, Monika Widyastuti (English Language Education Study Program, 2020)
Textbook is one of the essential parts of teaching and learning process. Textbook evaluation, therefore, is important to be carried out in order to get better quality in teaching and learning process. In the recent curriculum, curriculum 2013, the government assigned to use the course book When English Rings A Bell (WERB). However the textbook has some weaknesses. This article is aimed at describing the result of textbook evaluation done by the researcher based on the construct of criteria of good textbook derived from some experts of textbook evaluation. The findings show that WERB does not cover all of the English skills namely reading and writing. Second, WERB is not in accordance with the principles of scientific approach teaching procedures. Third, WERB does not provide authentic materials for the students. WERB contains very simple tasks. Based on the result of textbook analysis, it revealed that it is necessary to have supplementary materials in order to give additional materials.